Public Emergency Threatening the Life of the Nation - Michalska, Anna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2021)
The paper is an English translation of Niebezpieczeństwo publiczne, które zagraża życiu narodu by Anna Michalska, published originally in Polish in Prawa człowieka w sytuacjach nadzwyczajnych, ze szczególnym uwzględnieniem prawa i praktyki polskiej in 1997. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Department of Public International Law” devoted to the achievements of the representatives of the Poznań studies on international law.